Market Orientation dan Pengaruhnya terhadap Kinerja Perusahaan (Studi pada Hotel Non Bintang di Kabupaten Badung) - Wirga, I Wayan (Universitas Brawijaya, Indonesia, 2009)
The research goal is to find out the influence size of the practical aspect of marketing with market orientation which consists of sub-variables such as relationship oriented, fragmented oriented, and consumer oriented toward non stars hotel performance in Badung Regency. The type of this research is explanatory research. By using multiple regression analysis, the practical aspect of marketing with market orientation has significance influence towards non star hotel performance in Badung Regecy not only partially but also simultaneously. The strengths and weaknesses of the association is indicated by correlation coefficient of 71.3%, and the contribution of the practical aspect marketing with market orientation towards the industry performance is indicated by R square of 50.8%. The other result of this research is that the practical aspect of marketing with market orientation which focused on optimally internal performance (fragmented oriented) has the biggest influence towards industry performance that is 42.8%.